PRIORITAS ALTERNATIF PENINGKATAN KINERJA COMMUTERLINE DI MASA PANDEMI COVID-19 - Agustin, Imma Widyawati; Hariyani, Septiana; Damayanti, Sherly Oktafia (LPPM Universitas Terbuka, 2022)
Surabaya City is the National Activity Center in East Java which has a heterogeneous function andserves as the center of orientation for the activities of residents living in the surrounding area. Everyday many commuters are active in Surabaya City. The highest number of commuters came fromSidoarjo Regency with 169.560 people or 40% of the total 423.109 people. However, of the totalcommuters, only 1.246 people, or 0,7% of the 169.560 commuters rely on the commuter line, whilethe number of private vehicle users is 159.190 people. This causes congestion with the movementpattern of private vehicles in the Sidoarjo region to Surabaya with a volume of 3.491 pcu/hour withan LOS of 0,90 to 1,58. One of the government's efforts to reduce the use of private vehicles is toprovide mass transportation in the form of commuter lines. This study aims to evaluate the operationalperformance and service of the commuter line Surabaya-Pasuruan route to determine which aspectsneed to be prioritized to serve optimally. The data obtained through observation and questionnaireswere reviewed using operational performance analysis (load factor, headway, travel time, waitingtime), IPA, and QFD. The results of the operational performance analysis showed various problems,namely the load factor exceeding the 60% standard carrying capacity due to Covid-19 adaptation andwaiting time exceeding the maximum standard of 20 minutes. The priority of technical responsedirectives is obtained in improving operational and service performance, namely the periodicmaintenance and inspection of railway facilities.